Tertiary aquifers in the Slovenske Gorice and Goričko hills - Žlebnik, Ljubo (Geologija, 1978)
The land between the Mura and Drava rivers is a morphologic region made up of the Tertiary marly and clayey deposits interbedded with water bearing sand and gravel. The water occurs under sufficient hydrostatic pressure to rise above the topographic surface. In some restricted areas the mineral matter content and free carbon dioxide give it a pleasant taste. The Quaternary aquifers occurring in the adjacent Mura and Drava level fields are under water table conditions. Areally they are the most extensive and widely available source of fresh water. Thermal water was tapped in some places from the deep-seated Tertiary beds, underlying the Quaternary deposits. It is interesting to note the difference between the Miocene and Pliocene aquifers, as their hydraulic mechanisms are concerned. The geological conditions are favourable for the Pliocene aquifers. Their hydraulic characteristics depend upon the uplifted Sobota block which is considered to be a recharge area; here, highly permeable Pliocene beds appear at the land surface, overlying the northeast plunging metamorphic basement. On the other hand, the Sobota uplift is a ground-water barrier that prevents the free recharge of the deepseated Miocene aquifers in the Radgona and Ljutomer depressions. The most important hvdrogeologic parameters involved in the thermal and mineral aquifers were established from the pumping tests. The perennial yields and withdravals have been estimated and the question of the amount of recharge and discharge is discussed. The quantities of mineral and thermal waters in storage of the country have been estimated.